“Inovasi Fintech dan Manajemen Risiko Pasca-Pandemi: Kajian Bibliometrik Tren Riset Global" - Cindy Antika; Ahmad Muntadzir; Khaidar Rahmaini Jamila (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The acceleration of financial system digitalization in the post–COVID-19 period has positioned fintech innovation and risk management as strategic issues within international finance and business studies, alongside rising global economic uncertainty and increasing cross-border risk complexity. This study aims to map global research trends and identify dominant patterns in the literature on fintech innovation and post-pandemic risk management through a bibliometric-based literature review approach. The research employs a semi-systematic literature review by analyzing five relevant peer-reviewed journal articles, synthesized through thematic grouping and pattern-based analysis. The findings indicate a growing scholarly focus on the dual role of fintech as a driver of efficiency and financial inclusion, as well as a source of emerging non-traditional risks, while also revealing a persistent conceptual fragmentation between technological innovation and risk management frameworks. This study contributes to the international finance and business literature by offering an integrated overview of fintech and risk-related research trends and by highlighting avenues for more holistic and context-sensitive future studies.